Food Safety: High-Risk Foods Crossword - Linda B. Bobroff; Jennifer Hillan (EDIS)
Some foods are more likely to cause foodborne illness than others. Unpasteurized milk or juices are not safe to consume. Uncooked foods that are made with raw or undercooked eggs are especially risky. This revised 2-page fact sheet was written by Linda B. Bobroff and Jennifer Hillan, and published by the UF Department of Family, Youth and Community Sciences, February 2014.